The Caribbean story finder : a guide to 438 tales from 24 nations and territories, listing subjects and sources - Elswit, Sharon (McFarland & Company, Inc., Publishers, 2017)
"The Caribbean islands have a vibrant oral folklore. In Jamaica, the clever spider Anansi, who outsmarts stronger animals, is a symbol of triumph by the weak. Conflict over status, identity and power is a theme across the island nations. This volume summaries 438 tales retold in English and Creole from West African, European, and slave Indigenous cultures"--